Study on the path of clustering construction of rural primary schools’ aesthetic education programs from the perspective of resource integration - Zhankun Han; Yunhu Xie (PLoS ONE, 2025)
Aesthetic education is an important part of the overall development of students. This study analyzes the number of rural schools and enrollment, number of classes, and number of full-time teachers in those schools from 2013 to 2022, and clarifies the current challenges in aesthetic education in rural elementary schools and the path of quality improvement. It then constructs a curriculum cluster model that shares resources, teachers, management, instructional design, and practical activities, etc. The results find that (1) the number of rural primary schools in 2013–2022 shows a decreasing trend, and in 2022 there was a 45.77% decrease relative to 2013. The number of rural elementary schools in 2022 shows a decreasing trend, and the relative decrease in 2022 compared with 2013 is 45.77%. From 2013 to 2022, the number of elementary schools in rural areas was more than 50% of the total number of elementary schools. Rural elementary schools in China are scattered, the distribution rate of aesthetic education resources is low, and it is difficult to popularize high-quality aesthetic education resources. (2) The number of classes in China’s rural elementary schools decreased 30.28% from 1.139 million in 2013 to 788,000 in 2022. The small size of rural schools, small number of teaching classes, and small number of students lead to less investment in resources for schools to offer aesthetic education, and the integration of collective public art courses cannot be realized. (3) Using the model of a “two-dimensional aesthetic education curriculum cluster,” we can improve the high-quality development of aesthetic education in rural schools. (4) The design path of the aesthetic education curriculum clusters focuses on the implementation and implantation of teaching objectives, teaching design and teaching process by grade, and links interest activities, nature and social observation activities, etc. Organically with aesthetic education. This study can thereby an effective path for the improvement of the quality of aesthetic education in rural elementary schools and the high-quality development of aesthetic education in rural schools.